2012
DOI: 10.4103/0019-557x.99919
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment in urban school children of low-income families in Kolkata, India

Abstract: To evaluate pattern of visual impairment in school children from low-income families in Kolkata, India, an institutional cross-sectional study was conducted among 2570 children of 10 primary schools. Ocular examination including refraction was done and pattern of visual impairment and refractive error was studied. The age range was 6-14 years. Refractive error was seen in 14.7%. Only 4 children were already wearing correction. Myopia and hypermetropia was present in 307 (11.9%) and 65 (2.5%) children, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 75 publications
1
18
0
1
Order By: Relevance
“…[13] , and 14.7% in urban school children of lowincome families in Kolkata. [14] , but lower than the finding of prevalence of 23.67% refractive error in a study conducted at a Tertiary Eye Care Hospital in Kolkata. [15] However, the findings in this study are much higher than that of urban and rural Maharashtra of 5.46% and 2.63% respectively.…”
Section: Discussionmentioning
confidence: 54%
“…[13] , and 14.7% in urban school children of lowincome families in Kolkata. [14] , but lower than the finding of prevalence of 23.67% refractive error in a study conducted at a Tertiary Eye Care Hospital in Kolkata. [15] However, the findings in this study are much higher than that of urban and rural Maharashtra of 5.46% and 2.63% respectively.…”
Section: Discussionmentioning
confidence: 54%
“…Though the prevalence of myopia is low compared to those reported from other countries in East Asia [516], it is higher than those previously reported by studies from India [17–19] and Nepal [20]. Due to different refractive error cut offs, different sample population and different methodologies of the previous Indian studies, it is difficult to state whether this difference indicates an actual increase in the prevalence but 13.1% prevalence in children in a country of 1.2 billion with over 20% in 5–15 years age-group, implies that myopia is a significant public health problem in India.…”
Section: Discussionmentioning
confidence: 56%
“…In East Asia the prevalence of myopia has been reported to be very high particularly in Japan [5], South Korea [6,7], Singapore [8], Taiwan [9,10], Hong Kong [1112], and China [1316] though much lower rates have been reported from South Asia and India[17–21]. While there are no large scale studies in India for assessing the magnitude of myopia in the school going population, available studies show higher prevalence rates in urban areas compared to rural areas [17–19]. Besides risk of ametropic amblyopia in growing children and the inconvenience and cost of spectacles or contact lenses, 10–20% have high myopia predisposing them to severe irreversible visual impairment [22].…”
Section: Introductionmentioning
confidence: 99%
“…among urban school children of low-income families in Kolkata found that visual acuity of less than 6/12 in better eye was present in 4.2% children. 9 According to NPCB Survey (2001-02) among children 5-15 years of age, visual impairment was 6.4% as compared to 4.5% in present study. In Turkey (2009), Unsal A et.…”
Section: Discussionmentioning
confidence: 78%